Hormonal dynamics and transcriptomic regulatory mechanisms during seed dormancy release in Aconitum kusnezoffii - Yingtong Mu; Kefan Cao; Xiaojie Li; Xiaoming Zhang (PLoS ONE, 2026)
Aconitum kusnezoffii is an important medicinal plant whose seeds exhibit deep physiological dormancy. To elucidate the endogenous hormonal regulation mechanisms and dynamic gene expression patterns during dormancy release, we conducted a comprehensive analysis integrating hormone quantification and transcriptome sequencing on seed samples subjected to cold stratification for 0, 14, and 42 days. Morphological observations indicated that the embryo development rate remained stable during the first 14 days of stratification but increased significantly after 21 days, displaying a sigmoidal growth pattern. This provided a rationale for delineating the dormancy maintenance, release initiation, and pre-germination phases and for selecting key sampling time points. Hormonal profiling revealed a continuous decline in abscisic acid (ABA) content, accompanied by a gradual increase in germination-promoting hormones such as gibberellins (bioactive GA, reported as GA₃-equivalents), indole-3-acetic acid (IAA), brassinolide (BL) and methyl jasmonate (MeJA). The ratios of GA/ABA (GA₃-equivalents), IAA/ABA, and zeatin riboside (ZR; ELISA-based total tZR + cZR equivalents)/ABA increased accordingly, suggesting that dormancy release is orchestrated through a synergistic interplay of multiple hormones. Transcriptome analysis yielded 79,251 Unigenes, with differentially expressed genes significantly enriched in pathways related to energy metabolism, hormone signal transduction, and carbohydrate metabolism. STEM clustering identified five representative temporal expression profiles. Further analysis of hormone-related pathways showed that ABA biosynthesis and signaling components were predominantly active at early stages but declined thereafter, whereas GA and IAA biosynthetic and signaling genes were markedly upregulated during the later stages of dormancy release. These findings highlight the close association between embryo development and hormonal dynamics during seed dormancy release in A. kusnezoffii , and clarify the stage-specific features of hormone synthesis and signaling pathways, providing a theoretical basis for understanding dormancy mechanisms and improving artificial germination techniques.